2013
DOI: 10.1136/bmjopen-2013-003098
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of brainstem implicit learning paradigms differentiates multiple system atrophy (MSA) from idiopathic Parkinson syndrome

Abstract: ObjectivesLearning as measured by eyeblink classical conditioning is preserved in patients with idiopathic Parkinson's disease, but severely affected in patients with progressive supranuclear palsy. We here sought to clarify whether procedural learning is impaired in multiple system atrophy (MSA), and whether it may be helpful for the differentiation of parkinsonian syndromes.DesignWe investigated learning using (1) eyeblink classical conditioning with a delay (interstimulus interval 0 ms) and a trace (600 ms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…A similar effect can be observed using electrical methods to evoke the blink reflex. This kind of learning has been attributed to cerebellar circuits ( Dimitrova et al, 2002 ) and has been found abnormal in many disorders including some forms of dementia ( Woodruff-Pak, 2001 ), parkinsonisms ( von Lewinski et al, 2013 ), major depression ( Greer et al, 2005 ) and dystonia ( Janssen et al, 2014 ).…”
Section: Brain Stem Reflexes Including Startlementioning
confidence: 99%
“…A similar effect can be observed using electrical methods to evoke the blink reflex. This kind of learning has been attributed to cerebellar circuits ( Dimitrova et al, 2002 ) and has been found abnormal in many disorders including some forms of dementia ( Woodruff-Pak, 2001 ), parkinsonisms ( von Lewinski et al, 2013 ), major depression ( Greer et al, 2005 ) and dystonia ( Janssen et al, 2014 ).…”
Section: Brain Stem Reflexes Including Startlementioning
confidence: 99%